Pengembangan Game Belajar Huruf Hijaiyah Untuk Disleksia dengan Metode Waterfall - Agus Purnomo (JURIKOM (Jurnal Riset Komputer), 2023)
Dyslexia is a learning disability that is mainly related to literacy and language skills. In this study focused on hijaiyah letters. The goal to be achieved is to produce a game application that can be used by teachers to support learning hijaiyah letters for dyslexia.The waterfall method is used in game application development. One type of dyslexia is Visuo-spatial difficulties characterized by difficulties in writing, reading, remembering and mathematics. Learning tried to be applied is visual stimulation that is done repeatedly. To train the memory of dyslexia, the type of puzzle game was chosen. An easy game is presented, children just need to draft and drop hijaiyah letters according to the questions given, questions are presented in voice instructions. Successfully developed game applications can be run on android devices. Every game activity is recorded by a web-based monitoring system. Learning progress is presented in the form of statistical graphs that can be accessed by teachers.